Análisis financiero de la corporación de productores y comercializadores orgánicos Bio Taita Chimborazo, del cantón Colta, periodos 2019, 2020 y 2021. - Minagua Mullo, Sandra Elizabeth (2024)
ABSTRACT: In the country, non-profit organizations are the actors and the main basis for the economic and social growth of rural sectors. For this reason, financial information plays a fairly important role since through financial statements you can know the current economic situation in order to make future decisions regarding their well-being. In this context, the topic of study arises: Financial Analysis of the Corporation of Organic Producers and Marketers Bio Taita Chimborazo, of the Colta Canton, periods 2019, 2020 and 2021, with the purpose of carrying out an analysis of its financial situation. To carry out this analysis, a research methodology that combines qualitative and quantitative approaches has been used. This comprehensive approach has allowed detailed and contextualized information to be collected, providing a solid basis for evaluating the financial health of the organization and suggesting possible areas for improvement. Among the most relevant results are that COPROBICH faces difficulties in covering its short-term obligations, depending largely on the sale of inventories to maintain liquidity. In addition, there is an increase in leverage with creditors in 2020, although this was reduced in 2021. Internal collection management appears inefficient, negatively impacting portfolio recovery and cash availability. Finally, profitability is worrying, with a significant drop in profits, reaching losses in 2021. For this reason, it is recommended that the company use financial analysis tools to evaluate the economic situation of the company. In addition, with the results obtained, risks can be identified that may be significantly affecting the company.